Entre diversidade e diferença: o programa de Ações Afirmativas da UFSCar e as vivências dos estudantes indígenas - Jodas, Juliana (Universidade Federal de São Carlos, 2012)
This search staring of educational policies for higher education for the indigenous population from the Brazilian Federal Constitution of 1988, that, at least in law, obtained their rights guaranteed and their ethnic differences recognized. Since then two actions were created in this context: the course of Intercultural Degree and the Affirmative Action Program. The focus of this research is in the Affirmative Action policies for indians, understood as a set of measures of unequal access to basic goods such as education and employment for historically subordinate groups, and specially, the case of the Universidade Federal de São Carlos. This study analyzed the urgency context of Affirmative Action in Brazil and its deployment in the process of institutionalization of UFSCar, and particularly, how the indigenous students experience this recent experience. For this, this work includes a literature review and document analysis to characterize the Affirmative Action of UFSCar and understand how in its perspective, diversity or difference, the program has been constituted. We also interviews with indian students to understand their perception of the policy, their experiences, and in particular, will be discussed how their differences, subjectivities and/or identities are (or not) marked and recognized at this institutional space.
Keywords: Relações raciais; Grupos Indígenas; Ensino Superior; Ações Afirmativas; Diferença; Higher Education; Affirmative Action; Indigenous; Difference; CIENCIAS HUMANAS::SOCIOLOGIA